Biological maturity influences running performance in junior Australian football - Gastin, P. B.; Bennett, G.; Cook, J. (Journal of Science and Medicine in Sport, 2013)
The purpose of this study was to investigate the influence of biological maturity on measures of running fitness and running performance in both training and competition in junior Australian football.